Honeycomb demercuration catalyst prepared from waste SCR catalyst and preparation method of honeycomb demercuration catalyst
Through the compound acid treatment and mixture baking treatment on the waste SCR catalyst, the efficient honeycomb mercury removal catalyst is prepared, the problem of low immersion efficiency of waste SCR catalysts and insufficient catalytic immersion efficiency is solved, and efficient mercury removal and mechanical strength have been achieved.
Patent Information
- Application Number
- CN202411303370.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-19
- Publication Date
- 2025-01-28
AI Technical Summary
In the prior art, the leaching efficiency of the waste SCR catalyst is low, and the catalyticity of the honeycomb mercury demercury catalyst prepared by the regeneration waste SCR catalyst is insufficient, making it difficult to meet the requirements of efficient mercury demercury and mechanical strength.
By adding waste SCR catalysts grinding into powder to compound acid treatment agents, after cleaning and filtering, mixed with salt, tungsten salt, active additives, and removal water for forming slurry. After drying High mercury efficiency and mechanical strength honeycomb mercury removal catalyst.
Improve the immersion efficiency of the waste SCR catalyst, enhance the mercury loss efficiency and mechanical strength of the honeycomb mercury removal catalyst, and ensure the efficient application of catalysts.
Smart Images

Figure BDA0005048355820000081 
Figure BDA0005048355820000091 
Figure BDA0005048355820000101
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of catalysts, and in particular relates to a honeycomb mercury removal catalyst prepared from waste SCR catalysts and a preparation method thereof. Background Art
[0002] SCR catalyst refers to the heavy metal pollutants, alkaline (earth) metals, sulfur dioxide and other substances in the high content of ash in the flue gas during operation, which cause poisoning, wear and clogging of the SCR catalyst, resulting in a decrease in the denitrification performance of the SCR catalyst and inability to meet the use requirements, resulting in waste SCR catalyst. The waste SCR catalyst contains a large amount of titanium, tungsten and vanadium as well as oxides such as silicon, aluminum and calcium. The waste SCR catalyst still has a certain catalytic ability and can be used in other catalytic systems. Therefore, it is of great research significance to use the waste SCR catalyst to prepare a honeycomb catalyst and apply it to the catalysis of elemental mercury in real flue gas.
[0003] The recovery of spent SCR catalysts can be achieved through a wet method, which relies on acid or alkali to leach spent SCR catalysts, adjust the physical and chemical conditions of the solution, separate different components, and further recover and process them into the desired products. However, inorganic acids and alkalis are often used to treat spent SCR catalysts, which can easily cause pollution and have low leaching efficiency. After the spent SCR catalysts are treated with acid, vanadium ions and tungsten ions dissolved in the acid treatment agent are still adsorbed on the surface of the spent SCR catalysts, resulting in incomplete removal. The spent SCR catalysts after acid treatment are then mixed with active substances to prepare honeycomb demercuration catalysts, but the catalytic activity of the formed honeycomb demercuration catalysts for mercury needs to be improved. Summary of the invention
[0004] The purpose of this section is to summarize some aspects of embodiments of the present invention and briefly introduce some preferred embodiments. Some simplifications or omissions may be made in this section and the specification abstract and the invention title of this application to avoid blurring the purpose of this section, the specification abstract and the invention title, and such simplifications or omissions cannot be used to limit the scope of the present invention.
[0005] In view of the above problems and / or existing problems in the prior art, the present invention is proposed to improve the leaching efficiency of the waste SCR catalyst and prepare a honeycomb mercury removal catalyst from the regenerated waste SCR catalyst, which has high mercury removal efficiency and mechanical strength.
[0006] Therefore, the purpose of the present invention is to overcome the deficiencies in the prior art and provide a method for preparing a honeycomb mercury removal catalyst using waste SCR catalyst.
[0007] In order to solve the above technical problems, the present invention provides the following technical solutions: comprising:
[0008] (1) Adding the ground waste SCR catalyst into the composite acid treatment agent, washing and filtering to obtain a filtrate and acid-treated waste SCR catalyst powder.
[0009] (2) Acid-treated waste SCR catalyst powder, vanadium salt, tungsten salt, active additive, and deionized water are mixed to form a slurry, and the slurry is dried, placed in a honeycomb ceramic for calcination, and cooled to obtain a honeycomb mercury removal catalyst;
[0010] Wherein, the calcination temperature is 500-600° C. and the calcination time is 3-5 hours.
[0011] As a preferred embodiment of the method for preparing a honeycomb mercury removal catalyst using a waste SCR catalyst according to the present invention, the method for preparing the composite acid treatment agent comprises:
[0012] The adsorbent and tannic acid are dissolved in deionized water, stirred evenly, and then hydrochloric acid with a concentration of 2 to 3 mol / L is added, and the reaction is stirred at 36 to 38°C for 1 to 3 hours, filtered, washed with water, and dried to obtain a solid, and the solid, oxalic acid with a concentration of 1 mol / L and tartaric acid with a concentration of 0.5 mol / L are stirred evenly to obtain a composite acid treating agent.
[0013] Among them, the mass volume ratio of the adsorbent, tannic acid, deionized water and hydrochloric acid is (0.7-0.8) g: (1-2) g: (25-35) mL: (0.1-0.3) mL; the mass volume ratio of the solid, oxalic acid and tartaric acid is (0.1-0.3) g: (8-12) g: (15-25) mL.
[0014] The hydroxyl groups on the surface of the adsorbent can be combined with tannic acid through chemical bonds, so that the tannic acid is coated on the surface of the adsorbent, thereby improving the dispersibility of the adsorbent in the organic acid treatment agent. The mixed solution of oxalic acid and tartaric acid, as an acid treatment agent for the waste SCR catalyst, can be combined with the transition metal tungsten and vanadium ions in the waste SCR catalyst to form a soluble complex; the tannic acid coated on the surface of the adsorbent can be combined with oxalic acid and tartaric acid through chemical bonds to form a cross-linked network structure, and the adsorbent is dispersed in the cross-linked network structure. The tungsten and vanadium ions dissolved in the acid treatment agent can be adsorbed and fixed by the adsorbent, thereby preventing the metal tungsten and vanadium ions from still being adsorbed on the surface of the waste SCR catalyst carrier after the acid treatment.
[0015] As a preferred embodiment of the method for preparing a honeycomb mercury removal catalyst using a waste SCR catalyst of the present invention, the method for preparing the adsorbent comprises:
[0016] The organic precursor powder is dissolved in deionized water, stirred evenly, and modified bacterial cellulose is added. After negative pressure of -0.1 to -0.08 MPa for 8 to 12 minutes, the mixture is placed in a reaction kettle, subjected to hydrothermal treatment at 150 to 170°C for 1 to 2 hours, cooled to room temperature, and centrifuged at 7000 to 9000 r / min for 4 to 6 minutes to obtain a solid. The solid is rubbed with sandpaper to clean the surface particles to obtain an adsorbent.
[0017] The mass volume ratio of the organic precursor powder, deionized water and modified bacterial cellulose is (0.5-1.5) g: (15-25) mL: (2-3) g; and the organic precursor includes ginkgo leaves or sycamore leaves.
[0018] The organic precursor ginkgo leaf powder can be adsorbed into the pores of the zinc-based metal organic framework on the surface of modified bacterial cellulose. After hydrothermal treatment at 160°C for 1 hour, the organic precursor ginkgo leaf in the pores of the zinc-based metal organic framework undergoes a carbonization reaction to form carbon nuclei. As the reaction continues, the carbon nuclei gradually aggregate to form nanoscale carbon dots, thereby achieving the in situ synthesis of nanocarbon dots in the pores of the zinc-based metal organic framework on the surface of modified bacterial cellulose. The small size structure of the nanocarbon dots refines the pore size of the zinc-based metal organic framework, increases the adsorption capacity, and increases the adsorption of tungsten and vanadium ions in the waste SCR catalyst.
[0019] As a preferred embodiment of the method for preparing a honeycomb mercury removal catalyst using waste SCR catalyst of the present invention, the method for preparing the modified bacterial cellulose comprises:
[0020] The bacterial cellulose is dissolved in deionized water, and a zinc source is added after stirring to obtain a mixed solution. A 2-methylimidazole aqueous solution is added to the mixed solution, and the mixture is stirred for reaction for 1 to 3 hours, and then allowed to stand for 10 to 14 hours, filtered, washed with water, and water is replaced with tert-butyl alcohol, removed, and freeze-dried at -25°C to -15°C for 0.5 to 1.5 hours to obtain modified bacterial cellulose;
[0021] The mass volume ratio of the bacterial cellulose, deionized water, zinc source and 2-methylimidazole is (0.0.5-0.15) g: (45-55) mL: (2-3) g: (8-9) g; the zinc source includes one of zinc nitrate hexahydrate, zinc chloride and zinc acetate; the bacterial cellulose has a diameter of 3-5 nm and a length of 1-2 μm.
[0022] The zinc ion in the zinc source zinc nitrate hexahydrate acts as a central metal ion and can undergo a coordination reaction with the nitrogen atom in dimethylimidazole. The nitrogen atom of 2-methylimidazole acts as a ligand and combines with the zinc ion in the form of a coordination bond to form a crystal. The crystal grows and precipitates to form a metal-organic skeleton with a porous structure. In the reaction process, the zinc ion can combine with the hydroxyl group on the surface of the bacterial cellulose through a chemical bond to realize the synthesis of a zinc-based metal-organic skeleton on the surface of the bacterial cellulose. The bacterial cellulose acts as a carrier with a large specific surface area and can load a large amount of zinc-based metal-organic skeleton, thereby improving the adsorption performance of tungsten and vanadium ions in the waste SCR catalyst.
[0023] As a preferred embodiment of the method for preparing a honeycomb mercury removal catalyst using a waste SCR catalyst of the present invention, the waste SCR catalyst has a TiO2 content of 85.4% to 85.6%, a WO3 content of 4.3% to 4.4%, a V2O5 content of 0.64% to 0.66%, and the remainder is Fe, Al, and Si; the particle size of the waste SCR catalyst powder is 200 to 300 meshes; and the particle size of the acid-treated waste SCR catalyst powder is 400 to 500 meshes.
[0024] As a preferred embodiment of the method for preparing a honeycomb mercury removal catalyst using a waste SCR catalyst of the present invention, the concentration of the composite acid treatment agent is 1 to 3 mol / L.
[0025] As a preferred embodiment of the method for preparing a honeycomb mercury removal catalyst using a waste SCR catalyst according to the present invention, the method for preparing the active auxiliary agent comprises:
[0026] The glass fiber is added to hydrochloric acid with a concentration of 0.5 to 1.5 mol / L, stirred at 35 to 45° C. for 25 to 35 minutes, filtered, washed with water, and dried to obtain pretreated glass fiber, the pretreated glass fiber is added to n-butyl titanate, stirred evenly, a nitric acid solution with a concentration of 0.1 to 0.3 mol / L is added, stirred at 70 to 90° C. for 35 to 45 minutes, filtered, and dried to obtain glass fiber loaded with titanium dioxide sol;
[0027] Cerium nitrate and copper nitrate are mixed in a mass ratio of (0.5-1.5):(4-5) to obtain a nitrate complex;
[0028] The nitrate complex and the glass fiber loaded with titanium dioxide sol are added to deionized water, stirred evenly, polyethylene glycol is added, stirred, placed in a reaction kettle, sintered at 380-420° C. for 1-3 hours, and cooled to room temperature to obtain an active additive;
[0029] The mass volume ratio of glass fiber to hydrochloric acid is (0.3-0.7) g: (25-35) mL; the mass volume ratio of pretreated glass fiber to n-butyl titanate and nitric acid solution is (0.1-0.3) g: (8-9) mL: (45-55) mL;
[0030] The mass volume ratio of the nitrate complex, the glass fiber loaded with titanium dioxide sol, deionized water and polyethylene glycol is (5-6) g: (15-25) g: (15-25) mL: (0.5-1.5) g; the length of the glass fiber is 0.2-1 μm, and the diameter is 40-50 nm.
[0031] The glass fiber is mixed with tetrabutyl titanate. The hydroxyl groups on the surface of the glass fiber can be combined with the titanium hydroxyl groups produced by the hydrolysis of tetrabutyl titanate through chemical bonds, so as to synthesize titanium dioxide sol on the surface of the glass fiber, which can adsorb and fix cerium ions and copper ions in the nitrate complex.
[0032] The glass fiber loaded with titanium dioxide sol can adsorb and fix cerium ions and copper ions in the nitrate complex. After sintering at 400°C for 2 hours, the organic components in the nitrate complex are decomposed, so that cerium and copper are doped into titanium dioxide to form an active additive. The glass fiber in the active additive has a high aspect ratio and is interspersed between the honeycomb demercuration catalyst particles to improve the compactness. The glass fiber has high mechanical strength and compressive strength, which makes the honeycomb demercuration catalyst have high compressive resistance.
[0033] As a preferred embodiment of the method for preparing a honeycomb mercury removal catalyst using a waste SCR catalyst of the present invention, the vanadium salt comprises one or more of ammonium metavanadate or vanadium pentoxide; and the tungsten salt comprises one or more of ammonium metatungstate or ammonium paratungstate.
[0034] As a preferred embodiment of the method for preparing a honeycomb mercury removal catalyst using a waste SCR catalyst according to the present invention, the mass volume ratio of the acid-treated waste SCR catalyst powder, vanadium salt, tungsten salt, active additive, and deionized water is (35-45) g: (2-3) g: (3.3-3.6) g: (0.5-1.5) g: (40-50) mL.
[0035] The purpose of the present invention is to overcome the deficiencies in the prior art and provide a honeycomb mercury removal catalyst prepared using waste SCR catalyst.
[0036] Beneficial effects of the present invention:
[0037] (1) The present invention synthesizes a zinc-based metal organic skeleton on the surface of bacterial cellulose. The bacterial cellulose, as a carrier, has a large specific surface area and can load a large amount of zinc-based metal organic skeletons, thereby improving the adsorption performance of tungsten and vanadium ions in the waste SCR catalyst. Nanocarbon dots are in situ synthesized in the pores of the zinc-based metal organic skeleton on the surface of the modified bacterial cellulose. On the one hand, the small size structure of the nanocarbon dots refines the pore size of the zinc-based metal organic skeleton, improves the adsorption capacity, and increases the adsorption of tungsten and vanadium ions in the waste SCR catalyst. On the other hand, the nanocarbon dots, as the skeleton of the zinc-based metal organic skeleton, have high mechanical properties, thereby avoiding the collapse of the pores of the zinc-based metal organic skeleton and causing adsorption failure. In addition, the oxygen-containing functional groups contained in the nanocarbon dots can also adsorb and fix tungsten and vanadium ions in the waste SCR catalyst.
[0038] (2) The present invention uses a mixed solution of oxalic acid and tartaric acid as an acid treatment agent for the waste SCR catalyst. Oxalic acid can effectively remove sulfates that clog the pores in the waste SCR catalyst, so that the sulfates in the pores can be removed. Oxalic acid and tartaric acid are compounded to form soluble complexes with transition metal tungsten and vanadium ions in the waste SCR catalyst, which is beneficial to dissolve vanadium pentoxide and tungsten trioxide that have aggregated into clusters and crystals in the waste SCR catalyst, thereby improving the leaching rate.
[0039] (3) Tannic acid is coated on the surface of the adsorbent, which improves the dispersibility of the adsorbent in the organic acid treatment agent. The tannic acid coated on the surface of the adsorbent can combine with oxalic acid and tartaric acid through chemical bonds to form a cross-linked network structure. The adsorbent is dispersed in the cross-linked network structure, which increases the attachment sites for tungsten and vanadium ions in the waste SCR catalyst. In addition, tungsten and vanadium ions dissolved in the acid treatment agent can be adsorbed and fixed by the adsorbent, avoiding the metal tungsten and vanadium ions still adsorbed on the surface of the waste SCR catalyst carrier after acid treatment and aggregation, resulting in incomplete removal and affecting the recovery efficiency of metal ions.
[0040] (4) Titanium dioxide sol is synthesized on the surface of glass fiber, which can adsorb and fix cerium ions and copper ions in the nitrate complex. After sintering at 400°C for 2h, the organic components in the nitrate complex are decomposed, so that cerium and copper are doped into titanium dioxide to form an active additive. The copper element can inhibit the recombination of titanium dioxide electron-hole pairs in the acid-treated waste SCR catalyst. The cerium element has unique redox properties and can effectively promote the oxidation of mercury at a lower temperature, thereby improving the demercuration efficiency and photocatalytic activity. The cerium-doped catalyst has good sulfur resistance and can maintain a high demercuration efficiency in sulfur-containing flue gas, avoiding sulfur dioxide from generating sulfate on the demercuration catalyst to block the pores of the catalyst, resulting in the failure of the demercuration performance of the catalyst. The glass fiber in the active additive has a high aspect ratio and is interspersed between the particles of the honeycomb demercuration catalyst, thereby improving the compactness and the demercuration efficiency. The glass fiber has high mechanical strength and compressive strength, so that the honeycomb demercuration catalyst has high compressive resistance. DETAILED DESCRIPTION
[0041] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.
[0042] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.
[0043] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.
[0044] The raw materials used in the present invention are all commercially available unless otherwise specified.
[0045] The waste SCR catalyst used is a mixture of waste SCR catalysts with a TiO2 content of 85.4% to 85.6%, a WO3 content of 4.3% to 4.4%, and a V2O5 content of 0.64% to 0.66%; bacterial cellulose (Guilin Qihong Technology Co., Ltd.); hydrated zinc nitrate (Sinopharm Chemical Reagent Co., Ltd., AR); 2-methylimidazole (Shanghai Aladdin Biochemical Technology Co., Ltd., AR); ginkgo leaves (collected from Jiang'an Campus of Sichuan University and stored in a ventilated, cool and dry place); tannic acid (Fuchen Chemical); oxalic acid (glossy, fiber grade, purchased from Sinopec Baling Petrochemical Company); n-butyl titanate (Nanjing Tengchuan Technology Co., Ltd., purity of 99%); copper nitrate (Tesco Chemical (Hubei) Co., Ltd., purity of 99%); cerium nitrate (Shandong Desheng New Materials Co., Ltd.); polyethylene glycol (polyethylene glycol 400, Henan Jinchen Chemical Products Co., Ltd.).
[0046] The performance of the material prepared in the embodiment of the present invention was tested as follows:
[0047] The mechanical strength of the honeycomb mercury removal catalyst prepared above was tested on a YAW-300D pressure testing machine.
[0048] The prepared honeycomb demercuration catalyst was placed on a catalyst activity test bench and the mercury catalytic oxidation performance was evaluated using simulated flue gas. The initial flue gas conditions were: flue gas temperature 350°C, total gas flow rate 1L / min, oxygen concentration 6(v / v)%, NO concentration 350ppm, NH3 concentration 350ppm, SO2 concentration 1000ppm, H2O concentration 10(v / v)%, Hg concentration 50μg / m 3 .
[0049] Mercury oxidation efficiency was tested using a RA-915 mercury analyzer.
[0050] The contents of W and V in the filtrate after the acid treatment in step (3) were analyzed by inductively coupled plasma emission spectrometer (AOD-ICP-2060T). The waste SCR catalyst powder and the acid-treated waste SCR catalyst powder were washed with deionized water for multiple times, dried, and weighed, and the leaching rates (%) of W and V were calculated.
[0051] Example 1
[0052] This embodiment provides a method for preparing a honeycomb mercury removal catalyst using a waste SCR catalyst, specifically:
[0053] (1) Preparation of composite acid treatment agent:
[0054] Preparation of modified bacterial cellulose: Add 0.1 g of bacterial cellulose to 40 mL of deionized water, stir evenly, add 2.6 g of zinc nitrate hexahydrate, stir evenly to obtain a mixed solution, add 8.5 g of 2-methylimidazole to 10 mL of deionized water, stir evenly, add to the mixed solution, stir to react for 2 hours, let stand overnight, filter, wash with deionized water 3 times, replace the water with 30 mL of tert-butanol, remove, and freeze-dry at -20°C for 1 hour to obtain modified bacterial cellulose.
[0055] Preparation of adsorbent: Wash ginkgo leaves with deionized water, dry them in an oven at 65°C for 10 minutes, grind them into powder with a grinder, add 1g of powder into 20mL of deionized water, stir evenly, add 2.5g of modified bacterial cellulose, place it in a reactor at negative pressure of -1MPa for 10 minutes, hydrothermally treat it at 160°C for 1.5 hours, cool it to room temperature, centrifuge it at 8000r / min for 5 minutes to obtain a solid, rub the solid with sandpaper to clean the surface particles to obtain an adsorbent.
[0056] Add 0.75g of adsorbent and 1.5g of tannic acid to 30mL of deionized water, stir evenly, add 0.2mL of 3mol / L hydrochloric acid, stir and react at 37°C for 2h, filter, wash 3 times with deionized water, dry in an oven at 45°C for 1h to remove moisture to obtain a solid, stir 0.2g of the solid, 10mL of 1mol / L oxalic acid and 20mL of 0.5mol / L tartaric acid evenly to obtain a composite acid treating agent.
[0057] (2) Preparation of active additives:
[0058] Add 0.5 g of glass fiber to 30 mL of 1 mol / L hydrochloric acid, stir at 40 ° C for 30 min, filter, wash with deionized water three times, and dry in an oven at 70 ° C for 10 min to obtain pretreated glass fiber. Add 0.2 g of pretreated glass fiber to 8.5 mL of n-butyl titanate, mix well, add 50 mL of 0.2 mol / L nitric acid solution, stir and react at 80 ° C for 40 min, filter, and dry at 60 ° C for 10 min to obtain glass fiber loaded with titanium dioxide sol.
[0059] 5.5 g of nitrate complex and 20 g of glass fiber loaded with titanium dioxide sol are added to 20 mL of deionized water, stirred evenly, 1 g of polyethylene glycol is added, stirred, placed in a reactor, sintered at 400 ° C for 2 h, and cooled to room temperature to obtain an active additive, wherein the nitrate complex is mixed with cerium nitrate and copper nitrate in a mass ratio of 1:4.5.
[0060] (3) Preparation of honeycomb mercury removal catalyst:
[0061] The waste SCR catalyst was washed with water, dried in an oven at 90° C. for 35 min, and ground into powder in a zirconia ball mill to obtain waste SCR catalyst powder, wherein the particle size of the zirconia grinding beads was 4 mm, and the particle size of the waste SCR catalyst powder was 250 meshes.
[0062] 20 g of waste SCR catalyst powder was placed in 200 mL of a composite acid treatment agent with a concentration of 2 mol / , stirred and cleaned, and then passed through a 450-mesh sieve to obtain a filtrate and acid-treated waste SCR catalyst powder.
[0063] 40 g of acid-treated waste SCR catalyst powder, 2.5 g of ammonium metavanadate and 3.6 g of ammonium metatungstate, 1.5 g of an active agent, and 50 mL of deionized water were mixed to form a slurry. The slurry was dried in an oven at 90° C. for 35 min, placed in a honeycomb ceramic, calcined at 550° C. for 3.5 h, and cooled to room temperature to obtain a honeycomb mercury removal catalyst.
[0064] Example 2
[0065] The difference between this embodiment and embodiment 1 is that the calcination temperature in step (3) is adjusted to 500° C., and the rest of the preparation process is the same as that in embodiment 1 to prepare a honeycomb mercury removal catalyst.
[0066] Example 3
[0067] The difference between this embodiment and embodiment 1 is that the calcination temperature in step (3) is adjusted to 600° C., and the rest of the preparation process is the same as that in embodiment 1 to obtain a honeycomb mercury removal catalyst.
[0068] Comparative Example 1
[0069] The difference between this embodiment and embodiment 1 is that the calcination temperature in step (3) is adjusted to 400° C., and the rest of the preparation process is the same as that in embodiment 1 to prepare a honeycomb mercury removal catalyst.
[0070] Comparative Example 2
[0071] The difference between this embodiment and embodiment 1 is that the calcination temperature in step (3) is adjusted to 700° C., and the rest of the preparation process is the same as that in embodiment 1 to prepare a honeycomb mercury removal catalyst.
[0072] The performance of the material prepared in the above embodiment was tested, and the comparison results with those in Example 1 are shown in Table 1.
[0073] Table 1
[0074]
[0075] It can be seen from the above table that adjusting the calcination temperature has a significant effect on the performance of the honeycomb mercury removal catalyst. This is because the appropriate calcination temperature can optimize the pore structure of the catalyst, increase the specific surface area, and thus enhance its adsorption and catalytic effect on the reactants. According to the results in the above table, the best technical effect can be obtained when the calcination temperature in the present invention is 550°C.
[0076] Example 4
[0077] The difference between this embodiment and embodiment 1 is that in the preparation process of the adsorbent in step (1), the hydrothermal treatment temperature is adjusted to 150° C., and the rest of the preparation process is the same as that in embodiment 1 to prepare a honeycomb mercury removal catalyst.
[0078] Example 5
[0079] The difference between this embodiment and embodiment 1 is that in the preparation process of the adsorbent in step (1), the hydrothermal treatment temperature is adjusted to 170° C., and the rest of the preparation process is the same as that in embodiment 1 to obtain a honeycomb mercury removal catalyst.
[0080] The performance of the material prepared in the above embodiment was tested, and the comparison results with those in Example 1 are shown in Table 2.
[0081] Table 2
[0082]
[0083] It can be seen from the above table that adjusting the hydrothermal treatment temperature of the adsorbent has a significant effect on the performance of the honeycomb mercury removal catalyst. This is because the hydrothermal treatment synthesizes more nano-carbon dots in the pores of the zinc-based metal organic skeleton on the surface of the modified bacterial cellulose, which better refines the pore size of the zinc-based metal organic skeleton and improves the adsorption capacity. According to the results in the above table, the best technical effect can be obtained when the hydrothermal treatment temperature in the present invention is 160°C.
[0084] Example 6
[0085] The difference between this embodiment and embodiment 1 is that the sintering temperature of the active agent in step (2) is adjusted to 380° C., and the rest of the preparation process is the same as that in embodiment 1 to prepare a honeycomb mercury removal catalyst.
[0086] Example 7
[0087] The difference between this embodiment and embodiment 1 is that the sintering temperature of the active agent in step (2) is adjusted to 420° C., and the rest of the preparation process is the same as that in embodiment 1 to prepare a honeycomb mercury removal catalyst.
[0088] The performance of the material prepared in the above embodiment was tested, and the comparison results with those in Example 1 are shown in Table 3.
[0089] Table 3
[0090]
[0091] It can be seen from the above table that adjusting the sintering temperature of the active additive has a significant effect on the performance of the honeycomb mercury removal catalyst. This is because the optimal sintering temperature completely decomposes the nitrate complex, allowing cerium and copper to be doped into titanium dioxide, thereby improving the mercury removal efficiency and photocatalytic activity. According to the results in the above table, the best technical effect can be obtained when the sintering temperature in the present invention is 400°C.
[0092] Example 8
[0093] The difference between this embodiment and embodiment 1 is that in the preparation process of glass fiber loaded with titanium dioxide sol in step (2), the stirring reaction temperature is adjusted to 70° C. The rest of the preparation process is the same as that in embodiment 1 to prepare a honeycomb mercury removal catalyst.
[0094] Example 9
[0095] The difference between this embodiment and embodiment 1 is that in the preparation process of glass fiber loaded with titanium dioxide sol in step (2), the stirring reaction temperature is adjusted to 90° C. The rest of the preparation process is the same as that in embodiment 1 to prepare a honeycomb mercury removal catalyst.
[0096] The performance of the material prepared in the above embodiment was tested, and the comparison results with those in Example 1 are shown in Table 4.
[0097] Table 4
[0098]
[0099] It can be seen from the above table that adjusting the preparation temperature of the glass fiber loaded with titanium dioxide sol has a significant effect on the performance of the honeycomb demercuration catalyst. This is because the high or low reaction temperature affects the hydrolysis and polycondensation reaction rates of n-butyl titanate, resulting in insufficient reaction and an insufficiently dense structure of the generated titanium dioxide sol. According to the results in the above table, the best technical effect can be obtained when the stirring reaction temperature in the present invention is 80°C.
[0100] Comparative Example 3
[0101] The difference between this comparative example and Example 1 is that the adsorbent is adjusted to modified bacterial cellulose to prepare the composite acid treatment agent, and the rest of the preparation process is the same as that of Example 1 to prepare a honeycomb mercury removal catalyst.
[0102] Comparative Example 4
[0103] The difference between this comparative example and Example 1 is that no adsorbent is added to prepare the composite acid treating agent, and the rest of the preparation process is the same as that of Example 1 to prepare a honeycomb mercury removal catalyst.
[0104] Comparative Example 5
[0105] The difference between this comparative example and Example 1 is that glass fiber is not added to prepare the active auxiliary agent, and the rest of the preparation process is the same as that of Example 1 to prepare a honeycomb mercury removal catalyst.
[0106] Comparative Example 6
[0107] The difference between this comparative example and Example 1 is that no nitrate complex is added to prepare the active auxiliary agent, and the rest of the preparation process is the same as that of Example 1 to prepare a honeycomb mercury removal catalyst.
[0108] Comparative Example 7
[0109] This comparative example provides a method for preparing a honeycomb mercury removal catalyst from an existing waste SCR catalyst, specifically:
[0110] Negative pressure vacuuming: The waste SCR catalyst module is vacuumed for 20 minutes by a vacuum vacuuming device. The vacuum degree of the vacuum vacuuming device is 235mbar and the air volume is 265m 3 / h;
[0111] Cleaning: Place the waste SCR catalyst module after vacuuming in a 0.5 mol / l sulfuric acid solution for 10 min, rinse in deionized water for 5 min, then place the waste SCR catalyst module in a 0.1 mol / l sodium hydroxide solution for 10 min, and rinse in deionized water for 5 min;
[0112] Drying and crushing: the cleaned waste SCR catalyst module is dried at 180°C for 3 hours and then crushed to obtain SCR catalyst powder with a particle size of d50 = 4.54 μm;
[0113] Ingredients: SCR catalyst powder is mixed evenly with active material, binder (methyl cellulose) and lubricant (tung oil) in a weight ratio of 100:10:0.5:0.5, and then kneaded to obtain a slurry. Among them, the active material precursors are vanadium tetrachloride, cobalt chloride and tungsten chloride, and the weight ratio of vanadium tetrachloride, cobalt chloride and tungsten chloride is 2:3:5.
[0114] Extrusion molding: placing the obtained mud material into an extruder equipped with a honeycomb steel mold for extrusion molding to obtain a honeycomb mercury removal catalyst wet embryo;
[0115] Calcination: The obtained honeycomb demercuration catalyst wet embryo was dried and calcined at 500° C. for 3 h to obtain a honeycomb demercuration catalyst.
[0116] The performance of the material obtained in the above comparative example was tested, and the comparison results with those of Example 1 are shown in Table 5.
[0117] Table 5
[0118]
[0119] As can be seen from the above table, in Comparative Example 3, the adsorbent is replaced by a composite acid treatment agent prepared by modified bacterial cellulose, which is used for pickling the waste SCR catalyst. The leaching rate of W and V decreases, and the catalytic performance of the honeycomb demercuration catalyst is affected. This may be because the small size structure of the nanocarbon dots refines the pore size of the zinc-based metal organic skeleton, improves the adsorption capacity, and increases the adsorption of tungsten and vanadium ions in the waste SCR catalyst. The nanocarbon dots, as the skeleton of the zinc-based metal organic skeleton, have high mechanical properties, which avoids the collapse of the pores of the zinc-based metal organic skeleton and causes adsorption failure; in Comparative Example 4, a composite acid treatment agent prepared without adding an adsorbent is used for pickling the waste SCR catalyst. The leaching rate of W and V decreases, and the catalytic performance of the honeycomb demercuration catalyst is affected. This may be because the adsorbent is combined with oxalic acid and tartaric acid through chemical bonds to form a cross-linked network structure, and the tungsten and vanadium ions dissolved in the acid treatment agent can be adsorbed and fixed by the adsorbent, avoiding the metal tungsten and vanadium ions still adsorbed on the waste SCR catalyst after acid treatment. body surface; in comparative example 5, the active additive prepared without adding glass fiber is used to prepare the honeycomb demercuration catalyst with acid-treated waste SCR catalyst powder, and its mechanical strength and demercuration performance are reduced. This may be because the glass fiber has a higher aspect ratio and is interspersed between the honeycomb demercuration catalyst particles, thereby improving the compactness and the demercuration efficiency, and the glass fiber has higher mechanical strength and compressive strength; in comparative example 6, the active additive prepared without adding nitrate complex is used to prepare the honeycomb demercuration catalyst with acid-treated waste SCR catalyst powder, and its demercuration performance is reduced. This may be because the copper element can inhibit the electron-hole pair recombination of titanium dioxide in the acid-treated waste SCR catalyst, and the cerium element has unique redox properties and can effectively promote the oxidation of mercury at a lower temperature; the honeycomb demercuration catalyst prepared in comparative example 7, relative to the honeycomb demercuration catalyst prepared in the embodiment, shows that the honeycomb demercuration catalyst prepared by the present invention has better demercuration efficiency and mechanical strength, and during the acid treatment, the present invention has higher tungsten and vanadium leaching efficiency.
[0120] In summary, the honeycomb demercuration catalyst prepared by the present invention has good mechanical strength and demercuration performance. The waste SCR catalyst is washed with water, dried, and placed in a zirconia ball mill to grind into powder to obtain waste SCR catalyst powder. The waste SCR catalyst powder is placed in a composite acid treatment agent, washed, and filtered to obtain a filtrate and acid-treated waste SCR catalyst powder. The acid-treated waste SCR catalyst powder, vanadium salt, tungsten salt, active additive, and deionized water are mixed to form a slurry. After the slurry is dried, it is placed in a honeycomb ceramic for calcination and cooled to room temperature to obtain a honeycomb demercuration catalyst that meets the test performance requirements, while the honeycomb demercuration catalysts prepared in comparative examples 3 to 6 do not meet the performance requirements, indicating that the honeycomb demercuration catalyst prepared by the present invention has good mechanical strength and demercuration performance.
[0121] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the claims of the present invention.
Claims
1. A method for preparing a honeycomb mercury removal catalyst using waste SCR catalyst, characterized in that: include, The powdered waste SCR catalyst is added to the composite acid treatment agent, and the mixture is washed and filtered to obtain a filtrate and acid-treated waste SCR catalyst powder. Acid-treated waste SCR catalyst powder, vanadium salt, tungsten salt, active additive and deionized water are mixed to form a slurry, and the slurry is dried, placed in a honeycomb ceramic for calcination, and cooled to obtain a honeycomb mercury removal catalyst; Wherein, the calcination temperature is 500-600° C. and the calcination time is 3-5 hours.
2. The method for preparing a honeycomb mercury removal catalyst using a waste SCR catalyst according to claim 1, characterized in that: The preparation method of the composite acid treating agent comprises: The adsorbent and tannic acid are dissolved in deionized water, stirred evenly, and then hydrochloric acid with a concentration of 2 to 3 mol / L is added, and the mixture is stirred at 36 to 38°C for 1 to 3 hours, filtered, washed with water, and dried to obtain a solid, and the solid, oxalic acid with a concentration of 1 mol / L, and tartaric acid with a concentration of 0.5 mol / L are stirred evenly to obtain a composite acid treatment agent; Among them, the mass volume ratio of the adsorbent, tannic acid, deionized water and hydrochloric acid is (0.7-0.8) g: (1-2) g: (25-35) mL: (0.1-0.3) mL; the mass volume ratio of the solid, oxalic acid and tartaric acid is (0.1-0.3) g: (8-12) g: (15-25) mL.
3. The method for preparing a honeycomb mercury removal catalyst using a waste SCR catalyst as claimed in claim 2, characterized in that: The preparation method of the adsorbent comprises: The organic precursor powder is dissolved in deionized water, stirred evenly, and modified bacterial cellulose is added. After negative pressure of -0.1 to -0.08 MPa for 8 to 12 minutes, the mixture is placed in a reaction kettle, subjected to hydrothermal treatment at 150 to 170°C for 1 to 2 hours, cooled to room temperature, and centrifuged at 7000 to 9000 r / min for 4 to 6 minutes to obtain a solid. The solid is rubbed with sandpaper to clean the surface particles to obtain an adsorbent. The mass volume ratio of the organic precursor powder, deionized water and modified bacterial cellulose is (0.5-1.5) g: (15-25) mL: (2-3) g; and the organic precursor includes ginkgo leaves or sycamore leaves.
4. The method for preparing a honeycomb mercury removal catalyst using a waste SCR catalyst as claimed in claim 3, characterized in that: The method for preparing the modified bacterial cellulose comprises: The bacterial cellulose is dissolved in deionized water, and a zinc source is added after stirring to obtain a mixed solution. A 2-methylimidazole aqueous solution is added to the mixed solution, and the mixture is stirred for reaction for 1 to 3 hours, and then allowed to stand for 10 to 14 hours, filtered, washed with water, and water is replaced with tert-butyl alcohol, removed, and freeze-dried at -25°C to -15°C for 0.5 to 1.5 hours to obtain modified bacterial cellulose; The mass volume ratio of the bacterial cellulose, deionized water, zinc source and 2-methylimidazole is (0.0.5-0.15) g: (45-55) mL: (2-3) g: (8-9) g; the zinc source includes one of zinc nitrate hexahydrate, zinc chloride and zinc acetate; the bacterial cellulose has a diameter of 3-5 nm and a length of 1-2 μm.
5. The method for preparing a honeycomb mercury removal catalyst using a waste SCR catalyst according to claim 1, characterized in that: The TiO2 content of the waste SCR catalyst is 85.4% to 85.6%, the WO3 content is 4.3% to 4.4%, the V2O5 content is 0.64% to 0.66%, and the remainder is Fe, Al, and Si; the particle size of the waste SCR catalyst powder is 200 to 300 meshes; the particle size of the acid-treated waste SCR catalyst powder is 400 to 500 meshes.
6. The method for preparing a honeycomb mercury removal catalyst using a waste SCR catalyst according to claim 1, characterized in that: The concentration of the composite acid treatment agent is 1-3 mol / L.
7. The method for preparing a honeycomb mercury removal catalyst using a waste SCR catalyst according to claim 1, characterized in that: The preparation method of the active auxiliary agent, include, The glass fiber is added to hydrochloric acid with a concentration of 0.5 to 1.5 mol / L, stirred at 35 to 45° C. for 25 to 35 minutes, filtered, washed with water, and dried to obtain pretreated glass fiber, the pretreated glass fiber is added to n-butyl titanate, stirred evenly, a nitric acid solution with a concentration of 0.1 to 0.3 mol / L is added, stirred at 70 to 90° C. for 35 to 45 minutes, filtered, and dried to obtain glass fiber loaded with titanium dioxide sol; Cerium nitrate and copper nitrate are mixed in a mass ratio of (0.5-1.5):(4-5) to obtain a nitrate complex; The nitrate complex and the glass fiber loaded with titanium dioxide sol are added to deionized water, stirred evenly, polyethylene glycol is added, stirred, placed in a reaction kettle, sintered at 380-420° C. for 1-3 hours, and cooled to room temperature to obtain an active additive; The mass volume ratio of glass fiber to hydrochloric acid is (0.3-0.7) g: (25-35) mL; the mass volume ratio of pretreated glass fiber to n-butyl titanate and nitric acid solution is (0.1-0.3) g: (8-9) mL: (45-55) mL; The mass volume ratio of the nitrate complex, the glass fiber loaded with titanium dioxide sol, deionized water and polyethylene glycol is (5-6) g: (15-25) g: (15-25) mL: (0.5-1.5) g; the length of the glass fiber is 0.2-1 μm, and the diameter is 40-50 nm.
8. The method for preparing a honeycomb mercury removal catalyst using a waste SCR catalyst as claimed in claim 1, characterized in that: The vanadium salt includes one or more of ammonium metavanadate or vanadium pentoxide; the tungsten salt includes one or more of ammonium metatungstate or ammonium paratungstate.
9. The method for preparing a honeycomb mercury removal catalyst using a waste SCR catalyst as claimed in claim 1, characterized in that: The mass volume ratio of the acid-treated waste SCR catalyst powder, vanadium salt, tungsten salt, active additive and deionized water is (35-45) g: (2-3) g: (3.3-3.6) g: (0.5-1.5) g: (40-50) mL.
10. A honeycomb mercury removal catalyst prepared by the method according to any one of claims 1 to 9.
Citation Information
Cited By
Method for regenerating VOCs honeycomb catalyst at low temperature
CN122298527A